Recruitment Analysis on Employee Performance With Variable Control As Moderating On Manufacturing Company - Nashrudin Setiawan; Emi Wakhyuni; Nur Afrina Siregar (Yayasan Ilomata, 2020)
The analysis of this study aims to determine whether recruitment positive and significant effect on the performance of employees in the Manufacturing Company. To know able to moderate recruitment monitoring the performance of employees in the Manufacturing Company. Data analysis technique used is quantitative method with SPSS version 16.0. This study uses regression analysis moderating. The population in this study were all employees Manufacturing Company, and a sample of 44 respondents. The primary data using questionnaires. The results showed that recruitment positive and significant effect on the performance of employees in the Manufacturing Company. Supervision able to moderate recruitment to employee performance on a Manufacturing Company